Improved Performance of DFIG-generators for Wind Turbines Variable-speed - Ihedrane Yasmine; El Bekkali Chakib; Bossoufi Badre (Institute of Advanced Engineering and Science, 2018)
The following article presents the control of the power generated by the Doubly Fed Induction Generator, integrated into the wind system, whose rotor is linked to the power converters (Rotor Side Convert (RSC) and Grid Side Converter (GSC)) interfaced by the DC-BUS and connected to the grid via a filter (Rf, Lf) in order to obtain an optimal power to the grid and to ensure system stability. The objective of this study is to understand and to make the comparison between Sliding mode Control technique and the Flux Oriented Control in order to control the Doubly Fed Induction Generator powers exchanged with the grid, it also aims at maintaining the DC-BUS voltage constant and a unit power factor at the grid connection point.The results of simulation show the performance of the Sliding mode Control in terms of monitoring, and robustness with regard to the parametric variations, compared to the Flux Oriented Control. The performance of the systems was tested and compared with the use of MATLAB/Simulink software.